Molecular dynamics simulation of DTPA with CaCO3 and FeS - Abu Zar, Che Azimi; Norhayati, Abdullah; Fatmawati, Adam (The Malaysian Analytical Sciences Society, 2024)
In the production of oil and gas, calcium carbonate (CaCO3) and iron sulphide (FeS) are among mineral scale deposits mainly found in tubing and valves located at surface facilities, which have been a nuisance in the oil flow during processing. Diethylenetriaminepentaacetic acid (DTPA) has a greater affinity to form stable divalent metal ion complexes during chelation to facilitate the dissolution of oilfield solid scale. Octadentate DTPA chelating ligand occupies five carboxylic acids, and three amine groups provide potential binding sites. The interaction between the molecules in the system can be replicated through molecular dynamics simulation explicitly using a COMPASS force field and the Ewald summation method available in the Material Studio software. The radial distribution function (RDF) in simulation trajectory files was utilised to study intermolecular interactions. The RDF results showed strong hydrogen bonding between O—H2O and H5—DTPA at a distance of 1.75 Å. The intermolecular interaction of DTPA with H2O in the existing CaCO3 and FeS denotes the interaction shift from water to the metal ion. The carbonyl group of DTPA exhibited a more significant interaction at a radial distance of 2.25 Å and intensity of 8.81 for Fe2+ but lower in Ca2+, which is at 1.47. The amine in DTPA analysis confirmed the low intensity of CaCO3 at a distance of 5.75 Å and intensity of 1.07, and a distance of 2.25 Å and intensity of 1.01 for FeS. Meanwhile, amines in DTPA—CO3 2- and DTPA—S2- systems demonstrated the low interaction at the same distance of 4.75 Å. The interaction of Ca2+ with CO3 2- in the DTPA system exhibited a sharp peak and high-intensity interaction at a distance of 2.25 Å and 13.71 intensity. Nevertheless, a sharp and low-intensity peak appeared on the Fe2+—S2- in the DTPA system at a distance of 4.75 Å and 2.18 intensity. In conclusion, these findings suggest that the carbonyl group of DTPA has a stronger interaction with Fe2+ than Ca2+. Meanwhile, the hydroxyl group of DTPA shows the highest intensity of interaction with CO3 2. Additionally, Ca2+ ions form more significant interactions with CO3 2- ions in the DTPA systems.